Analisis Perbandingan User Experience Shopee & TikTok Shop dengan System Usability Scale dan Usability Testing - Alfredo Herijanto; Andeka Rocky Tanaamah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Shopee and TikTok Shop are companies engaged in online shopping, commonly referred to as e-commerce. With the rapid advancement of technology, both platforms continue to grow and compete by offering features that aim to enhance user convenience. Among the two, Shopee demonstrates certain advantages over TikTok Shop. This raises the question of what factors contribute to Shopee’s superiority whether it is due to its product recommendation algorithm or overall usability. This study aims to examine the accuracy of product recommendation algorithms and evaluate usability using the System Usability Scale (SUS) and the ISO 9241-11 usability framework. The results show that the average SUS score for Shopee is 69.50, placing it in the "marginal" acceptability range with a grade of C, while TikTok Shop scores 67.43, also in the "marginal" range but with a grade of D. Based on usability testing aligned with ISO 9241-11, the effectiveness score for Shopee is 58.89% compared to TikTok Shop's 55.78%; efficiency is 51.33% for Shopee and 48.00% for TikTok Shop; and satisfaction is 16.00% for Shopee versus 14.67% for TikTok Shop. Additionally, the accuracy of Shopee’s product recommendation algorithm is 78.83%, outperforming TikTok Shop’s 73.33%. These findings indicate that Shopee surpasses TikTok Shop in both recommendation algorithm accuracy and usability aspects.